Diversity management in a sample of South African companies - Jacques B. Strydom; Ronel Erwee (South African Journal of Business Management, 1998)
An interview schedule was used to test the applicability of the Cox model of diversity management in a sample of South African companies. Even though this sample acknowledges the potential advantages of diversity, they do not yet experience a pressing need to optimise diversity in their workforce. This sample can be classified mainly as monolithic companies, although some evidence emerged that specific companies are developing a plural orientation. The applicability of an American model in a South African setting is discussed.
Keywords: 650